INNOVATIVE APPROACHES FOR TREATING INFECTIOUS LUNG DISEASES: A PARADIGM SHIFT IN RESPIRATORY MEDICINE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Infectious lung diseases, encompassing a spectrum from tuberculosis and pneumonia to emerging viral respiratory infections, remain a formidable challenge to global healthcare systems. These diseases exact a heavy toll in terms of morbidity and mortality, compelling the scientific community to continually seek innovative treatment methods. While conventional therapies such as antibiotics and antivirals have been invaluable, the rising tide of drug resistance and inherent limitations necessitate a fresh perspective on managing these ailments.